Right portal vein embolization with absolute ethanol in major hepatic resection for hepatobiliary malignancy. Issue 9 (11th June 2014) - Sofue, K.; Arai, Y.; Shimada, K.; Takeuchi, Y.; Kobayashi, T.; Satake, M.; Sugimura, K.
<x xml:space="preserve">Abstract</x> Background This study aimed to evaluate the safety and efficacy of preoperative right portal vein embolization (PVE) with absolute ethanol in patients with hepatobiliary malignancies. Methods PVE was performed via a percutaneous transhepatic ipsilateral approach, and the right portal branch was embolized with absolute ethanol. Technical success and complications following PVE, and changes in liver enzyme levels were evaluated. Changes in future liver remnant (FLR) and FLR/total functional liver volume ratio were calculated. Complications following hepatic resection were assessed. Results A total of 83 patients with hepatobiliary malignancies (53 men, 30 women; mean age 68 years) underwent right PVE. Tumour types were hilar cholangiocarcinoma (37), liver metastases (14), gallbladder cancer (13), intrahepatic cholangiocellular carcinoma (10) and hepatocellular carcinoma (HCC) (9). PVE was performed successfully in all patients. Four patients (5 per cent) developed complications following PVE (liver abscess 2, left portal vein thrombosis 1, pseudoaneurysm 1), but this did not preclude hepatic resection. Liver enzyme levels rose transiently after PVE. The mean FLR and FLR/total functional liver volume increased after PVE (from 366 to 513 cm3 and from 31 to 43 per cent respectively; both P < 0·001). Changes in the FLR and FLR/total functional liver volume ratio were comparable between patients with HCC and those with other malignancies (42 and 44 per cent, and 12 and 12 per cent, respectively). Sixty‐nine of 83 patients underwent hepatic resection at a median of 25 days after PVE, with no postoperative mortality. Conclusion Preoperative right PVE with absolute ethanol is safe and effective for induction of selective hepatic hypertrophy in patients with hepatobiliary malignancy.